Pandangan Tokoh Masyarakat Pada Perilaku Pasangan Calon Pengantin Selama Masa Khitbah di Kelurahan Gebang Kecamatan Patrang Kabupaten Jember - Mahmud Suyuti (Rechtenstudent, 2021)
The khitbah period is a period of introduction for the prospective bride and groom to get the heart to carry out the marriage. During this period, there are things that must be considered by the prospective bride and groom, namely regarding ethics or behavior during the sermon in accordance with Islamic law. Therefore, there are no rights and obligations between the two of them and it is forbidden to see as it is forbidden to see between men and women who are not husband and wife or their mahram. This research uses a case study approach and this type of research is qualitative with juridical-empirical methods or field research. The research location is in Gebang Village, Patrang District, Jember Regency. The research subjects used primary data and secondary data. Data collection techniques with interviews, observation and documentation. The results of this study are: 1) The behavior of the prospective bride and groom in the Gebang Village does not comply with Islamic religious rules, male and female couples who have made a proposal, the perpetrators assume that they are allowed to do some activities such as husband and wife, but do not cross the line that should be. . 2) The views of community leaders towards the prospective bride and groom during the sermon are those who are already engaged only as a relationship bond that will lead to a more serious level. However, the bride and groom must obey Islamic law, such as not going out together without being accompanied by a guardian, unless they are directly married to sirri. 3) A review of Islamic law on the behavior of the prospective bride and groom considers that the khitbah does not change the legal status of the relationship between a man and a woman, it's just that with the khitbah the two have a closer bond. In Islam for relationships that have not been mahram has been regulated very strictly.